A review of neurocognitive functioning of children with sex chromosome trisomies: Identifying targets for early intervention. Issue 1 (11th July 2019) - Urbanus, Evelien; van Rijn, Sophie; Swaab, Hanna
Abstract: Sex chromosome trisomies (SCT) are among the most common chromosomal duplications in humans. Due to recent technological advances in non‐invasive screening, SCT can already be detected during pregnancy. This calls for more knowledge about the development of (young) children with SCT. This review focused on neurocognitive functioning of children with SCT between 0 and 18 years, on domains of global intellectual functioning, language, executive functioning, and social cognition, in order to identify targets that could benefit from early treatment. Online databases were used to identify peer‐reviewed scientific articles using specific search terms. In total 18 studies were included. When applicable, effect sizes were calculated to indicate clinical significance. Results of the reviewed studies show that although traditionally, the focus has been on language and intelligence (IQ) in this population, recent studies suggest that executive functioning and social cognition may also be significantly affected already in childhood. These findings suggest that neuropsychological screening of children diagnosed with SCT should be extended, to also include executive functioning and social cognition. Knowledge about these neurocognitive risks is important to improve clinical care and help identify targets for early support and intervention programs to accommodate for the needs of individuals with SCT. Abstract : With regard to the first aim, the reviewed studies collectively gave the following results. On the domain of global intellectual functioning (GIF), seven eight studies report outcomes in children between the ages of 4–18 years, with three studies focusing on children from the age of four years, and four five studies studying school‐aged children. To our knowledge, there were no studies that examined GIF in children with SCT before the age of four years. On the domain of language development, five seven studies reported outcomes in children between the ages of 2–18 years. To our knowledge, there were no studies that examined language development in children with SCT before the age of two years. Of the seven studies, two studies used only parent reports, the other three studies used either a performance task or a combination of parent report and performance tasks.